Análise espacial dos óbitos por tuberculose no estado do Maranhão - SANTOS, Vandiel Barbosa (2018)
INTRODUCTION: TB is an infectious disease that despite the decline in incidence and mortality rates remains a major public health problem in Brazil and worldwide. Maranhão is in the group of priority states for the fight against TB, in view of its deficient social and economic indicators that support the maintenance of TB cases, and consequently with the death outcome. OBJECTIVE: To analyze the spatio-temporal distribution of tuberculosis deaths in the State of Maranhão in the years 2010 to 2015. METHODS: This is an ecological study of tuberculosis deaths in the state of Maranhão, reported in the Information System and Notification Diseases and in the Mortality Information System, from 2010 to 2015, with the municipalities as the analysis unit. A descriptive analysis of TB deaths in Maranhão was made using the TB mortality coefficient as an indicator. For the study of the spatial pattern was used the global Moran index, as well as the correlogram and scattering of the Moran index. Aiming to capture the spatial correlation between neighboring municipalities, different regression models with conditionally autoregressive structure (CAR) were adjusted. RESULTS: Between 2010 and 2015, 949 deaths were reported for tuberculosis in Maranhão, Moran identified a strong spatial dependence on the occurrence of deaths by its neighboring peers. The municipalities that presented high mortality rates were: Brejo de Areia, Junco do Maranhão, Governador Nunes Freire and São Luís. Areas of vulnerability to TB occurrence include the municipalities of São Luís, Imperatriz, Grajaú, Caxias (São Mateus do Maranhão, Alto Alegre do Maranhão, Coroatá, Peritoró, São Luís Gonzaga do Maranhão, Bacabal and Pirapemas). Through the adjusted CAR model, it was found that approximately 12% of the municipalities have more than a 75% chance of TB death, and that the north and central part of the state are the regions that have the highest probability of death byTB. CONCLUSIONS: The spatial dependence of the TB mortality rate of a given area is affected by the rates of neighboring areas.